An Integration of Local Cultural Values in Family Planning Counseling in Indonesia: A Systematic Review of Effectiveness and Acceptability - Rona Riasma Oktobriariani; Rochmawati (The Indonesian Institute of Science and Technology Research, 2026)
Indonesia faces complex challenges in Family Planning programs due to cultural diversity, with more than 300 ethnic groups. This systematic review aims to identify models for integrating local cultural values into family planning counseling and evaluate their effectiveness in improving program acceptability. Literature searches were conducted through Google Scholar, Garuda Portal, PubMed, and DOAJ for the 2014-2024 period. Of the 74 articles identified initially, after a screening and feasibility assessment process, 10 articles were included in this review using the thematic narrative synthesis method. The results identified five models of cultural integration: (1) habituation of religious values that increase the understanding of family planning in a religious framework, (2) innovative communication strategies through social media that increase the reach of family planning information, (3) adaptation of family structure in family planning counseling, (4) technology integration in KIE based on Islamic values, and (5) development of counselors' cultural competence. The cultural competence of counselors in understanding family structures, privacy norms, and local moral values is a determinant of success. The integration of technology in KIE with cultural sensitivity shows great potential in the dissemination of family planning information. This research contributes to the development of a culturally adaptive family planning counseling framework that can increase the continuation rate and reduce the contraceptive dropout rate in Indonesia.